2005
DOI: 10.1172/jci23241
|View full text |Cite
|
Sign up to set email alerts
|

Nasal vaccination with a proteosome-based adjuvant and glatiramer acetate clears β-amyloid in a mouse model of Alzheimer disease

Abstract: Amyloid β-peptide (Aβ) appears to play a key pathogenic role in Alzheimer disease (AD). Immune therapy in mouse models of AD via Aβ immunization or passive administration of Aβ antibodies markedly reduces Aβ levels and reverses behavioral impairment. However, a human trial of Aβ immunization led to meningoencephalitis in some patients and was discontinued. Here we show that nasal vaccination with a proteosome-based adjuvant that is well tolerated in humans plus glatiramer acetate, an FDA-approved synthetic cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
115
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(125 citation statements)
references
References 61 publications
10
115
0
Order By: Relevance
“…These results questioned the role of T cells in Cop-1-mediated neuroprotection, and led us to postulate additional mechanisms mediating Cop-1-induced neuroprotection. Based on the observations made in this report and previously published works [11,12,16,18,49], we suggest that in neurodegenerative conditions, Cop-1 can affect neuroprotective outcomes by at least two independent mechanisms: (i) DC, directly delivering Cop-1 to injury sites where Cop-1 is released and directly affecting neurons, and (ii) induction of T cell-mediated response. This dual effect likely produces the rapid and long-lasting effect of Cop-1 during disease [11, 12, 15-17, 23, 50-52].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These results questioned the role of T cells in Cop-1-mediated neuroprotection, and led us to postulate additional mechanisms mediating Cop-1-induced neuroprotection. Based on the observations made in this report and previously published works [11,12,16,18,49], we suggest that in neurodegenerative conditions, Cop-1 can affect neuroprotective outcomes by at least two independent mechanisms: (i) DC, directly delivering Cop-1 to injury sites where Cop-1 is released and directly affecting neurons, and (ii) induction of T cell-mediated response. This dual effect likely produces the rapid and long-lasting effect of Cop-1 during disease [11, 12, 15-17, 23, 50-52].…”
Section: Discussionsupporting
confidence: 71%
“…Cop-1 elicits neuroprotective responses in animal models of neuroimmune, neurodegenerative, metabolic, and traumatic disorders [14]. This includes, but is not limited to, optic nerve injury [11], head trauma [15], Parkinson's disease [12], Alzheimer's disease [16], HIV-1-encephalitis [13], glaucoma [17], and experimentally induced encephalitis [18].…”
Section: Introductionmentioning
confidence: 99%
“…Untreated Tg-AD mice showed consistent and long-lasting impairments in spatial memory tasks. In contrast, performance of the MWM test by the GA-vaccinated Tg-AD mice was rather similar, on average, to that of their age-matched naïve non-Tg littermates (triangles; n ϭ 6) [three-way ANOVA, repeated measures: groups, df (2,16), F ϭ 22.3, P Ͻ 0.0002; trials, df (3,48), F ϭ 67.9, P Ͻ 0.0001; days, df (3,48), F ϭ 3.1, P Ͻ 0.035, for the acquisition phase; and groups, df (2,16), F ϭ 14.9, P Ͻ 0.0003; trials, df (3,48), F ϭ 21.7, P Ͻ 0.0001; days, df (1,16), F ϭ 16.9, P Ͻ 0.0008, for the reversal phase].…”
Section: Discussionmentioning
confidence: 99%
“…AD progression has been attributed, in part, to the microgliamediated local immune response, which apparently does not operate in the optimal way needed to fight off the adverse conditions (3,4). Studies from our laboratory have shown that recovery from CNS injury is critically dependent on the well controlled activity of T cells directed to specific CNS autoantigens (5,6).…”
mentioning
confidence: 99%
“…A second generation of candidate therapeutics has included a series of attempts to inhibit the formation of amyloid plaques. Active (16)(17)(18)(19)(20)(21)(22)(23) and passive (24) immunization approaches are presently being tested. However, some patients in the active human immunization trials have developed meningoencephalitis (25,26).…”
mentioning
confidence: 99%